Evaluation of drug likeliness of (Z)-4-((4-hydroxy-3-methoxy benzylidene)amino)-1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazol-3-one by computational analysis against coronavirus and T-cells of immune system (Indian Journal of Chemistry (IJC), 2023)
The Schiff base (Z)-4-((4-hydroxy-3-methoxy benzylidene)amino)-1,5-dimethyl-2-phenyl-1,2-dihydro-3H-pyrazole-3-one (VAP) has been synthesized by the condensation of 4-aminoantipyrine with vanillin and and characterized by FT-IR, 1H and 13C NMR spectroscopy. The structure of the synthesized compound has been confirmed by single-crystal X-ray diffraction studies, which shows that four units of the compound are in an asymmetric part of the crystal structure. The potential activity of synthesized Schiff base compound has been determined by molecular docking with T-cells (6bnk) and against Coronavirus (6lu7).